Urban mosques in the Horn of Africa during the medieval period - Carolina Cornax-Gómez; Jorge de Torres Rodríguez (Revue des Mondes Musulmans et de la Méditerranée)
Between the 13th and the 16th centuries, the Horn of Africa experienced a series of major transformations which made this zone one of the most dynamic regions in the continent. These historical processes included the consolidation of Muslim principalities in the region, the expansion of Islam among Somali nomads, the development of an urban network and the strengthening of existing political and trade links with the rest of the world. Throughout these changes, Islam and its material expressions – the mosque being the most obvious one – became one of the key factors of cohesion and stability in an increasingly conflicted world. Based on seven years of archaeological fieldwork in Somaliland, this paper will analyse the characteristics – style, architectural features, orientations – of the mosques documented in the permanent settlements of Somaliland. It will also analyse them within their wider context (either settlements, religious settlements or nomadic territories), and it will compare them with examples of neighbouring regions in the Horn of Africa like Ethiopia or Djibouti. It will also discuss the possible existence of regional styles and architectural influences in the development of mosques in Somaliland, within the wider context of the arrival and expansion of Islam in the region.